Predicted habitat and areas of ecological significance shifts of top predators in the South Shetland Islands under climate changes - Dai, Yufei; Yan, Denghui; Liu, Yu; Zhong, Mingding; Gao, Minhao; Cheng, Hao; Deng, Wenhong; Wu, Fuxing (Frontiers in Marine Science, 2025)
The South Shetland Islands, a critical area for primary productivity within the Southern Ocean, are significantly affected by global climate change. Seabirds and marine mammals, highly sensitive to ecological changes, are considered sentinel species within the ecosystem. Monitoring top predators and identifying Areas of Ecological Significance (AES) are essential for enhancing biodiversity conservation effectiveness and addressing future climate changes. This study employed the MaxEnt model and Zonation method to predict the distribution of suitable habitats and AES for 14 top predators in the South Shetland Islands under current and future climate scenarios. Key findings include: 1) The spatial distribution of top predators in the South Shetland Islands is predominantly influenced by bathymetry, mixed layer thickness (Mlotst), and sea ice concentration (SIC). 2) The highly suitable habitats for the Gentoo Penguin (Pygoscelis papua), Humpback Whale (Megaptera novaeangliae), and Light-mantled Albatross (Phoebetria palpebrata) are expected to decrease under various future scenarios. 3) The AES in the South Shetland Islands are predominantly concentrated along the southern coastal areas. 4) The AES on the western side of the islands are projected to undergo significant fluctuations, while those on the eastern side are likely to exhibit minor changes, with the central area remaining relatively stable.